FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN DI DESA POHUWATO TIMUR KECAMATAN MARISA KABUPATEN POHUWATO - Darmiati Dahar (Fakultas Pertanian Universitas Ichsan Gorontalo, 2016)
The welfare of fishermen is strongly influenced by their catch. If their catch a lot, so their income was also good and otherwise. This research aims to determine the factors that affect the income of fishermen and determine the factors that most influence on the income of fishermen in the village of East Pohuwato. The sampling technique in this research is using simple random sampling. The total sample of 76 respondents. The analysis tool used to test the hypothesis used multiple analysis or multiple regression. The results showed that of the five independent variables is capital, work experience, the distance of fishing, catch, and the prices are simultaneously significant effect on the income of fishermen. Meanwhile is partially variables that significantly affect the income of fishermen in the village of East Pohuwato is capital, their catch, and the price. While the variable of work experience and the distance of fishing in partial not significant effect on the income of fishermen village East Pohuwato.